PENGARUH PROMOSI, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN INDOSAT IM3 (Studi pada Komunitas IM3 Mahasiswa Perguruan Tinggi Negeri di Semarang) - Sarah Basbeth; Wahyu Hidayat; Sari Listyorini (Jurnal Ilmu Administrasi Bisnis, 2016)
IM3 is a provider that targeting the youth market. With a well-known fare cheap, IM3 should be able to maintain and even increase the benefits of its products. However, the advantages offered by IM3 seem not optimal. Many complaints submitted by customers to the company through social media, are about the signal strength is week, the difficulty of accessing the data, the IM3 employees that are not friendly enough, the active period of the card which is not long, and so forth. So that these things will obviously affect customer satisfaction. The purpose of this study is to determine the promotion effect of product quality and brand image to customer satisfaction in using Indosat IM3. This type of research is explanatory research. The population in this research is IM3 Community in Undip and Unnes in the number of samples taken is 100 respondents. The sampling technique in this study using non probability sampling with with purposive sampling technique. The analysis method used is cross tabulation, correlation, determination, simple linear regression, multiple, t test and F test with SPSS version 16.Based on the survey results revealed that the promotion, quality product and brand image have positive and significant impact to customer satisfaction, either partially or simultaneously. Independent variable that has the greatest influence on customer satisfaction is a variable of brand image.The advice that can be given is to give a briefing to the IM3 employees in order to be friendly towards the customers, make the active period of the card longer, extend the network signal so that the customers can access data quickly and they can recommend IM3 to people around them.